Tissue CA-19.9 content in colorectal adenomas and its value in the assesment of dysplasia Detección de CA-19.9 citosólico en adenomas colorrectales: Utilidad en el diagnóstico de la displasia - I. Salces; I. Vegh; S. Rodríguez-Muñoz; F. Colina; A. Pérez; S. Soto; F. Sánchez; J. de la Cruz; J. A. Solís-Herruzo (Revista Espanola de Enfermedades Digestivas, 2004)
Background: occasionally, the risk of malignant transformation may be difficult to establish in adenomatous polyps due to the fact that they contain areas with variable grades of dysplasia. A measurement of tissue tumor markers may be useful to recognize these adenomas. Objectives: the aims of this study were: to establish firstly the relationship between carbohydrate antigen 19.9 (CA-19.9) content in the colorectal mucosa and the characteristics of polyps, and secondly, the diagnostic value of the former's measurement. Patients and methods: tissue CA-19.9 concentration was measured in 155 colorectal samples obtained from 145 patients (21 normal mucosa; 113 adenomatous polyps; 21 adenocarcinoma). Cytosol CA-19.9 content was determined by enzyme-linked immunoadsorbant assay, and the measurement of this protein was achieved by quantitative assay. Tissue samples were also processed for histological examination. Results: we demonstrated that CA-19.9 levels in adenomatous polyps and adenocarcinomas were significantly higher than in the normal mucosa. These levels varied significantly according to polyp size, histological type, and grade of dysplasia. CA-19.9 contents were higher in polyps with a high risk of malignant transformation than in those with a low risk of severe dysplasia. The cut-off value 214 U/mg of protein properly differentiated both types of risk. The area under the receiver operating characteristic (ROC) curves showed that cytosol CA-19.9 levels allow classifying polyps according to their histological features. Conclusions: we concluded that the measurement of CA-19.9 content in adenomatous polyps may be useful to classify these tumors and confirm the feasibility to separate adenomas into two groups: low and high risk of malignant change. Introducción: en ocasiones, el riesgo de transformación maligna de los pólipos adenomatosos es difícil de identificar por existir zonas con distintos grados de displasia simultáneamente. La determinación tisular de los marcadores tumorales puede ser útil para clasificar estos adenomas. Objetivos: conocer la relación existente entre las tasas de antígeno carbohidratado 19.9 citosólico (CA-19.9) del tejido colónico y las características morfológicas de los pólipos, para posteriormente valorar la utilidad diagnóstica de esta medición. Pacientes y métodos: se estudiaron histológicamente 155 muestras de colon (21 muestras de mucosa normal, 113 pólipos adenomatosos y 21 adenocarcinomas) en las que además se determinó la concentración tisular de CA-19.9 mediante enzimoinmunoanálisis. Resultados: los niveles de CA-19.9 citosólico en los pólipos adenomatosos y los adenocarcinomas fueron significativamente más altos que los encontrados en la mucosa normal. En los adenomas, estos niveles variaban significativamente con el tamaño, el tipo histológico y el grado de displasia. El contenido de CA-19.9 tisular en los pólipos con alto grado de displasia fue mayor que en los de bajo riesgo de displasia. La tasa de 214 U/mg de proteína diferenció adecuadamente ambos tipos de pólipos. Al estimar las áreas bajo las curvas de eficacia diagnóstica se demostró que los niveles citosólicos de CA-19.9 permiten clasificar los pólipos adenomatosos de acuerdo con sus características histológicas. Conclusiones: la determinación tisular de CA-19.9 puede ser útil en la evaluación de los pólipos adenomatosos y confirma la posibilidad de clasificar los adenomas en dos grupos: bajo y alto grado de transformación maligna.